LINC00659 Inhibits Hepatocellular Carcinoma Malignant Progression by Blocking Aerobic Glycolysis through FUS Recruitment and SLC10A1 Modulation - Bin Chen; Xin Xu; Wei Wu; Ke Zheng; Yijun Yu (Analytical Cellular Pathology)
Hepatocellular carcinoma (HCC) is a malignant type of liver cancer that poses severe threat to human health worldwide. Aerobic glycolysis is a hallmark of HCC and facilitates its progression. Solute carrier family 10 member 1 (SLC10A1) and long intergenic non-protein coding RNA 659 (LINC00659) were detected to be downregulated in HCC cells, yet their potential functions underlying HCC progression remained unidentified. In the current work, colony formation and transwell assays were used to detect HCC cells (HepG2 and HuH-7) proliferation and migration in vitro study. The quantitative real-time polymerase chain reaction (qRT-PCR) and western blot assays were used for gene/protein expression determination. Seahorse assay was performed for aerobic glycolysis assessment. RNA immunoprecipitation (RIP) and RNA pull-down assays were conducted for detection of the molecular interaction between LINC00659 and SLC10A1. The results showed that overexpressed SLC10A1 significantly suppressed the proliferation, migration, and aerobic glycolysis in HCC cells. Mechanical experiments further demonstrated that LINC00659 positively regulated SLC10A1 expression in HCC cells by recruiting fused protein in sarcoma (FUS). Our work elucidated that LINC00659 inhibited HCC progression and aerobic glycolysis via the FUS/SLC10A1 axis, revealing a novel lncRNA–RNA-binding protein–mRNA network in HCC, which might provide potential therapeutic targets for HCC.